Effect of pedal cadence on the accumulated oxygen deficit, maximal aerobic power and blood lactate transition thresholds of high-performance junior endurance cyclists - Woolford, S. M.; Withers, R. T.; Craig, N. P.; Bourdon, P. C.; Stanef, T.; McKenzie, I. (European Journal of Applied Physiology, 1999)
Our findings emphasise that pedal cadence specificity is essential when assessing the cycling economy, AOD and blood lactate transition thresholds of high-performance junior endurance cyclists.